Speech and language deficits in children with selective mutism - cause, comorbidity, or consequences? - Drljan, Bojana (Specijalna edukacija i rehabilitacija, 2022)
Introduction. Selective mutism (SM) is a disorder described from two aspects, psychological and language disorders. Researchers mainly focused on the psychological dimension of SM. However, there is an increasing number of studies indicating a significant speech and language (SL) impairment in children with SM and the possible connection between difficulties in language development and the occurrence of SM at school age. Objective. The aim of this paper was to review available research on SL deficits in children with SM, in order to clarify the cause-and-effect relationships between language and anxiety disorders in these children. Methods. Databases of the Library Consortium of Serbia and relevant Internet search engines were used for the literature search. Results. Nine research studies on SL abilities in children with SM are available in the literature. Mixed and expressive types of developmental language disorder, developmental phonological disorder, and language processing deficits are the most common SL impairments in children with SM. They occur significantly more frequently in children with SM than in children with anxiety disorders without SM and typically developing children. These deficits are often associated with learning disorders, social skills difficulties, and the risk of behavioral problems at school age. Conclusion. Existing studies have provided valuable insights into some aspects of the SL development in children with SM. However, the relationship between language deficits and anxiety symptoms is still not clear. Research on the early SL development in these children, which could shed light on the complex cause-and-effect dynamics of language and anxiety disorders seen in children with SM, is particularly scarce.
Keywords: selective mutism; speech-language deficits; etiological factors; comorbidity